Recovery responses of acidified Finnish lakes under declining acid deposition - Vuorenmaa, Jussi (Finnish Environment Institute, 2013)
The present work provides a regional-scale assessment of the changes in acidifying deposition in Finland over the past 30 years and the current pattern in the recovery of acid-sensitive lakes from acidification in relation to changes in sulphate deposition. This information is needed for documenting the ecosystem benefits of costly emission reduction policies and further actions in air pollution policy. The development of sulphate deposition in Finland reflects that of European SO2 emissions. Before the 1990s, reductions in sulphur emissions in Europe had been relatively small and sulphate deposition showed no consistent trends. Due to emission reduction measures that were then taken, sulphate deposition started to clearly decline from the late 1980s. The bulk deposition of sulphate has declined 40-60% in most parts of the country during 1990-2003. The decline in sulphate deposition exceeded the decline of base cation deposition, which resulted in a decrease in acidity and acidifying potential of deposition over the 1990s. Nitrogen deposition also decreased since the late 1980s, but less than that of sulphate, and levelling off during the 1990s. Sulphate concentrations in all types of lakes throughout Finland have declined from the early 1990s. The relative decrease in lake sulphate concentrations (average 40-50%) during 1990-2003 was rather similar to the decline in sulphate deposition, indicating a direct response to the reduction in deposition. There are presently no indications of elevated nitrate concentrations in forested headwater lakes. Base cation concentrations are still declining in many lakes, especially in south Finland, but to a lesser extent than sulphate allowing buffering capacity (alkalinity) to increase. The recovery has been strongest in lakes in which sulphate has been the major acidifying agent, and recovery has been the strongest and most consistent in lakes in south Finland. The recovery of lakes in central Finland and north Finland is not as widespread and strong as observed in south. ...